Hubungan Dukungan Keluarga dengan Kepatuhan Pasien dalam Pengobatan Tuberkulosis di UPT Puskesmas Pahandut Kota Palangka Raya - Pratama, Daniel Ari; Widiarti, Astri; Immanuela Toemon, Agnes; Mutiasari, Dian; Trinovita, Elsa (Barigas: Jurnal Riset Mahasiswa, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which most attacks the lungs. Treatment adherence is influenced by family support and encouragement from health workers. The World Health Organization (WHO) reports around 10 million people worldwide suffer tuberculosis. The Palangka Raya City Health Office in 2021 reported 417 cases tuberculosis and 53 cases at Pahandut Health Center. This study was to know relationship of family support and patient compliance treatment in Puskesmas Pahandut. This study uses descriptive-analytic method with cross-sectional. Sampling was done by purposive sampling. Amount of 40 samples in accordance inclusion criteria were analyzed using Chi Square statistical test. This study was conducted at Pahandut Health Center in October-November 2022. The sample in this study were tuberculosis patients in category I aged 17-70 years lived in working area of Pahandut Health Center. There was relationship between family support and patient compliance in tuberculosis treatment with p-value 0.017.